L'innovation pédagogique en question : analyse des discours de praticiens - Denis Lemaître
Pedagogical innovation is perceived as a general injunction in higher education today. However, when we examine discourse and practice, we find that this expression covers a range of quite different realities in terms of ends, usage and ideological concepts. This is a study of the proceedings of the colloquium Questions de pédagogie dans l'enseignement supérieur, « Innover : comment et pourquoi ? » ("Pedagogical Issues in Higher Education, "Innovate : why ? How ?"), using the discourse analysis method, to reveal the concepts conveyed by pedagogical practitioners, teachers and researchers. This study highlights the most common characteristics of what the authors consider to be pedagogical innovation, around the production of tools and the will to adapt the students to contemporary social, economic and cultural realities. A widely-shared, pragmatic and positivist approach is apparent, presenting pedagogical innovation as an adaptation to the market conditions of higher education and employment, rather than a means of intellectual and moral emancipation of the students.